Eosinophilic angiocentric fibrosis of nasal septum: a case report - Ravikumar, Gayatri; Ananthamurthy, Anuradha; Kini, Usha (International Journal of Advances in Medicine, 2017)
Eosinophilic Angiocentric Fibrosis (EAF) is an uncommon benign condition involving the sinonasal tract and rarely the larynx and orbit. Its etiology still remains unclear, although some studies have hypothesized it as a form of IgG4-related systemic disease. Histologically EAF is characterised by the presence of mixed inflammatory cells with eosinophil predominance in the early stage, followed by concentric layers of sclerosis around the small caliber vessels in the late stage. The rarity of this condition, tumor like presentation and oblivious etiology, makes it an interesting entity. We hereby report one such rare case of EAF, since the awareness of this entity is essential to make an accurate diagnosis.